2003
DOI: 10.1002/meet.1450400149
|View full text |Cite
|
Sign up to set email alerts
|

Use scenarios in the development of the Alexandria Digital Earth Prototype (ADEPT)

Abstract: A user-centered, iterative design philosophy requires a common language between users, designers and builders to translate user needs into buildable specifications. This paper details the rationale, evolution and implementation of use scenarios-structured narrative descriptions of envisioned system use-in the development of the Alexandria Digital Earth Prototype. This paper discusses the strengths of the scenario approach, obstacles to their use, and lessons learned in the overall development process.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2005
2005
2006
2006

Publication Types

Select...
3
1

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…We interviewed faculty and students before and after the introduction of the alpha prototype and assessed the usability of the software. Results from these studies were used to write use case scenarios and enhanced software specifications for second‐generation prototypes (Ancona, Freeston, Smith, & Fabrikant, 2002; Coleman, Smith, Buchel, & Mayer, 2001; Gazan et al, 2003). Substantial design changes resulted from these iterative evaluations, such as creating a three‐screen display rather than a single‐screen display for teaching, building separate modules for creating lectures, concept maps, and examples, and constructing personal digital libraries that could import content from instructors' collections.…”
Section: Background and Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…We interviewed faculty and students before and after the introduction of the alpha prototype and assessed the usability of the software. Results from these studies were used to write use case scenarios and enhanced software specifications for second‐generation prototypes (Ancona, Freeston, Smith, & Fabrikant, 2002; Coleman, Smith, Buchel, & Mayer, 2001; Gazan et al, 2003). Substantial design changes resulted from these iterative evaluations, such as creating a three‐screen display rather than a single‐screen display for teaching, building separate modules for creating lectures, concept maps, and examples, and constructing personal digital libraries that could import content from instructors' collections.…”
Section: Background and Literature Reviewmentioning
confidence: 99%
“…Conversely, technologies that are adopted may be suboptimal in design, but succeed because they provide sufficient value to their audience (Rogers, 1995). Earlier research by the ADEPT Education and Evaluation Team has explored geographic education, digital library design, and the practices and goals of faculty, teaching assistants, and students (Borgman et al, 2000; Borgman, Leazer, Gilliland‐Swetland, & Gazan, 2001; Borgman et al, 2004; Champeny et al, 2004; Gazan et al, 2003; Gilliland‐Swetland & Leazer, 2001; Leazer, Gilliland‐Swetland, Borgman, & Mayer, 2000; Mayer, Mautone, & Prothero, 2002; Mayer, Smith, Borgman, & Smart, 2002). Research on the conceptual and technical development of ADEPT has been reported by the implementation and knowledge teams (Borgman, 2004; Hill & Freeston, 2003; Hill & Janee, 2004; Hill, Janee, Dolin, Frew, & Larsgaard, 1999; Janee & Frew, 2002; Janee, Frew, & Hill, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…and scientific reasoning sets completed by students. Details of the collection of this data can be found in Borgman, Leazer et al, 2001;Borgman, Smart et al, 2004;Champeny, Borgman et al, 2004;Gazan, Leazer et al, 2003;Leazer, Gilliland-Swetland et al, 2000.…”
Section: Methodsmentioning
confidence: 99%
“…More specifically, how can technology drive a curriculum based on hypothesis formulation rather than rote memorization to foster "active learning" (Dewald and Clair, 1997;Modell and Michael, 1993)? Efforts to answer this question have resulted in research by the evaluation and education team on geographic education, digital library design, and the practices and goals of faculty, teaching assistants, and students (Borgman, Gilliland-Swetland, Leazer, Mayer, Gwynn, Gazan and Mautone, 2000;Borgman, Leazer, Gilliland-Swetland and Gazan, 2001;Gazan, Leazer, Borgman, Gilliland-Swetland, Smart and al., 2003;Gilliland-Swetland and Leazer, 2001;Leazer, Gilliland-Swetland, Borgman and Mayer, 2000;Mayer, Mautone and Prothero, 2002).The conceptual and technical design and development of the ADEPT system has been led by the University of California, Santa Barbara (http://www.alexandria.ucsb.edu/research/index/htm) (Hill and Freeston, 2003;Hill, Carver, Larsgaard, Dolin, Smith, Frew and Rae, 2000;Janee, 2003;Janee and Frew, 2002). …”
mentioning
confidence: 99%